2021
DOI: 10.1111/jth.15334
|View full text |Cite
|
Sign up to set email alerts
|

Gene and protein expression in human megakaryocytes derived from induced pluripotent stem cells

Abstract: Background There is interest in deriving megakaryocytes (MKs) from pluripotent stem cells (iPSC) for biological studies. We previously found that genomic structural integrity and genotype concordance is maintained in iPSC‐derived MKs. Objective To establish a comprehensive dataset of genes and proteins expressed in iPSC‐derived MKs. Methods iPSCs were reprogrammed from peripheral blood mononuclear cells (MNCs) and MKs were derived from the iPSCs in 194 healthy European American and African American subjects. m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…Most importantly, the authors found a very high concordance of tissue-specific expression quantitative trait loci in both iMKs and platelets, validating this platform for studying the genetics of platelet-related phenotypes. In support, an extension of this study by demonstrated very good agreement between gene expression in iMKs and previous studies in which megakaryocytes were derived from cord blood or bone marrow sources, confirming that iMKs are a relevant model for native megakaryocytes [26 ▪ ]. They also observed that both sex and race have significant effects on differential gene expression but not differential protein expression.…”
Section: Validation Of Pluripotent Stem Cell-derived Megakaryocytessupporting
confidence: 88%
See 1 more Smart Citation
“…Most importantly, the authors found a very high concordance of tissue-specific expression quantitative trait loci in both iMKs and platelets, validating this platform for studying the genetics of platelet-related phenotypes. In support, an extension of this study by demonstrated very good agreement between gene expression in iMKs and previous studies in which megakaryocytes were derived from cord blood or bone marrow sources, confirming that iMKs are a relevant model for native megakaryocytes [26 ▪ ]. They also observed that both sex and race have significant effects on differential gene expression but not differential protein expression.…”
Section: Validation Of Pluripotent Stem Cell-derived Megakaryocytessupporting
confidence: 88%
“…In native megakaryocytes, these characteristics are lowest in yolk sac-derived megakaryocytes and higher in fetal liver-derived, cord blood-derived, and bone marrow-derived megakaryocytes [54,55,57,58]. (Bottom) Pluripotent stem cell-derived megakaryocytes (iMKs) are strong models for yolk-sac hematopoiesis [26 ▪ ,60]. For disease modeling, induced pluripotent stem cells are particularly advantageous because they are patient-specific and can be edited with technology such as CRISPR-Cas9 to produce isogenic controls.…”
Section: Limitations Of Current Imk Modelsmentioning
confidence: 99%
“…and mediators of immune relevance ( IL1B , IL8 , CXCL1 , CXCL2 , TGFBI etc.) ( Cunin and Nigrovic, 2019 ; Kammers et al, 2021 ). resVAE also managed to identify other biologically meaningful genes missed by Seurat, including a cell surface receptor on B cells involved in isotype switching ( CD40 ; Bishop and Hostager, 2001 ), a cell adhesion molecule expressed on T cells that is a well-known marker for naïve and memory cells ( SELL ; Yang et al, 2011 ), a pro-inflammatory cytokine expressed on NK cells ( IL32 ; Yang et al, 2019 ) and more ( Figure 3E ).…”
Section: Resultsmentioning
confidence: 99%
“…Details on the iPSC derived MK and PLT samples used in the RNA sequencing are described in detail elsewhere (Kammers et al, 2017; Kammers, Taub, Mathias, et al, 2021; Kammers, Taub, Rodriguez, et al, 2021). Briefly, for 185 iPSC‐derived MK cell lines and for 290 PLT samples with WGS data we also obtained RNA‐seq data from extracted nonribosomal RNA.…”
Section: Methodsmentioning
confidence: 99%